The Regeneration Potential of Kasa (Castanopsis acuminatissima Blume) in Kalaena Nature Reserve, East Luwu Regency - witno, Witno; Azis Karim, Hadijah; Praboowo, Arbin; Batari Putri, Andi Utami (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Kasa is one of the important species among 120 species in the genus Castanopsis (Fagaceae), which thrives in secondary and primary lowland forest areas up to 1000 m above sea level. This plant species exhibits tolerance to full sunlight. The objective of this study is to assess the regeneration potential of Kasa (Castanopsis acuminatissima Blume) in the Kalaena Nature Reserve, Indonesia. The research plots consisted of two 50 m x 50 m plots, with a nested 10 m x 10 m subplot placed using purposive sampling. The findings regarding the regeneration potential of Kasa in the Kalaena Nature Reserve revealed varying numbers of seedlings, saplings, poles, and trees. The regeneration potential of Kasa is influenced by the growth stages of seedlings and trees. During the seedling phase, the regeneration potential of Kasa is classified as very good. However, the density of trees, although in the productive category, is low due to environmental factors and the characteristics of the parent tree. Conversely, the sapling and pole phases exhibit very poor regeneration potential. In plot 1, there were 1964 individual seedlings, 6 individual saplings, 4 individual poles, and 21 individual trees. Meanwhile, plot 2 recorded 844 individual seedlings, 5 individual saplings, 1 individual pole, and 18 individual trees. The growth of Kasa in both plots displayed a clustered pattern.